2013
DOI: 10.7785/tcrt.2012.500253
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Activated Microbubble Cancer Therapy: Ceramide Production Leading to Enhanced Radiation Effect in vitro

Abstract: Blood vessels within tumours represent a key component for cancer cell survival. Disruption of these vessels can be achieved by inducing vascular endothelial-cell apoptosis. Moreover, endothelial cell apoptosis has been proven to be enhanced by ceramide-increasing drugs. Herein, we introduce a novel therapeutic approach which uses ultrasound-stimulated microbubbles used in combination with radiation to cause a rapid accumulation of ceramide in endothelial cells in-vitro. We also test this modality directly wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 15 publications
3
46
2
Order By: Relevance
“…This proof of principle research has been demonstrated in vitro Nofiele et al, 2013) and in vivo in a prostate cancer model (Czarnota et al, 2012a,b), in an in vivo bladder cancer model , and using a breast cancer model (unpublished results).…”
Section: Microbubble-based Enhancement Of Radiation Cell Death Effectsmentioning
confidence: 75%
See 2 more Smart Citations
“…This proof of principle research has been demonstrated in vitro Nofiele et al, 2013) and in vivo in a prostate cancer model (Czarnota et al, 2012a,b), in an in vivo bladder cancer model , and using a breast cancer model (unpublished results).…”
Section: Microbubble-based Enhancement Of Radiation Cell Death Effectsmentioning
confidence: 75%
“…Exposure parameters are similar to that used with diagnostic ultrasound scans, with the exception that greater quantities of microbubbles are used to elicit an effect. On their own, the ultrasound effects described here result in minimal damage from which tissues recover but, when combined with radiation, result in striking amounts of cell death in tumours (AlMahrouki et al, 2012;Czarnota et al, 2012a,b;Tran et al, 2012;Nofiele et al, 2013).…”
Section: Microbubbles and Ultrasoundmentioning
confidence: 91%
See 1 more Smart Citation
“…The experiments were conducted using packed RBCs donated by healthy volunteers recruited by the Canadian Blood Services' Network Center for Applied Development (Vancouver, BC, CA). 1 ml of control blood sample and 1 ml of blood with 50 µM of C2-ceramide (Sigma Aldrich, ON, CA) were prepared to induce eryptosis [5]. The two vials were kept in an incubator at 37 o C and 280 RPM using Incu-Shaker (Benchmark Scientific, NJ, USA).…”
Section: Sample Preparationmentioning
confidence: 99%
“…Microbubble shell disruption and gas release induces damage to the endothelial cells lining the vessels, thus resulting in subsequent vessel collapse [3], [4]. The damaged endothelial cells undergo apoptosis which have been shown to rapidly produce ceramide in the process [5]. Ceramide and phosphocholine are produced through the hydrolysis of sphingomyelin (part of the phospholipid bilayer) by acid sphingomyelinase (ASMases).…”
Section: Introductionmentioning
confidence: 99%